The Moderating Role of Psychological Well-Being on The Relationship Between Compensation and Employee Performance - Jahroni Jahroni; Didit Darmawan (CV. Ulil Albab Corp, 2024)
This study aims to examine the effect of compensation on employee performance with psychological well-being as a moderating variable in Islamic banks in Sidoarjo. Using quantitative methods with a survey approach, data were collected from 100 Islamic bank employees who met certain criteria. The results showed that compensation has a significant influence on employee performance. In addition, psychological well-being is proven to strengthen the effect of compensation on employee performance, which indicates the importance of psychological well-being in maximizing the effectiveness of compensation. This research provides an important contribution for management in designing a fair compensation system and effective welfare programs to improve employee performance.